OPTIMASI TEMPERATUR DAN ARUS UNTUK MENGHASILKAN TEGANGAN 12 VOLT DC PADA THERMOELECTRIC GENERATOR MODEL SP 1848-27145 SEBAGAI ACCUMULATOR CHARGER - Cekdin, Cekmas; Rahmayani, Siska (JURNAL SURYA ENERGY, 2017)
One source of potential energy with new innovations, namely the use of thermoelectric generator. Utilization of thermoelectric generators as a Heat power plant requires further study or research to produce an optimal system so that it can be a source of electrical energy substitutes in the provision of electrical energy. The working principle of the heat power plant is the first thermoelectric generator heated by filament where between filament and thermoelectric generator coated sheet metal. If the temperature of the heated metal is greater than the temperature of the metal heat dissipation, so experienced certain temperature difference difference, then the temperature difference causes a thermoelectric generator starts to work optimally. Measurement of Thermoelectric Generator with model number SP 1848-27145 carried out a total of 11 experiments on different materials with the same method. It consists of 4 modules compiled series, saddled lamp dc 12 Volt, 5 Watt. Optimization for charging the accumulator is 12 volts dc with temperature 270C and with a current that is obtained is 3.01 Ampere.